Animasi 2D Sebagai Media Edukasi Tentang Inner Child Untuk Generasi Z - Faiz Dwiardha, Diokta; Khoirul Anwar, Ahmad; Wibowo, Yudi (Universitas Sahid Surakarta, 2024)
Generation Z or Gen Z is the generation born between 1997 and 2012. Based on official data from the Indonesian Central Statistics Agency (BPS) in the 2020 population census. With the development of technology, it will greatly affect lifestyle, mindsets, experiences, psychology, and so on. With today's technological developments, it will greatly influence lifestyle patterns and lifestyles, thought patterns, experiences, psychology, and so on in each generation. The reason this happens is because of the parenting style, experiencing trauma and bad events in childhood, experiencing violence, confession, rejection from an environment, penance, TIP and so on. The impact is that a person can have negative childhood trauma and emotional wounds which can then cause a person to experience various mental health disorders, behave like a child, and lack wisdom in dealing with life's problems as an adult. Therefore, an educational video was designed in the form of animation based on the results of psychological interview data and several journal articles as reference material. This design method has 5 stages, namely Development, Pre-Production, Production, Post-Production and Distribution. The result is 2D animation and merchandise. The hope of designing this 2D animation is that it can provide solutions and insight into the inner child which has such an impact on a person's life so that they are mentally healthy and achieve. Keywords: Designer, 2D Animation, Mental Health Disorder, Inner Child, Design Methods, Generation Z.